Influence of vanadium concentration and temperature on the preparation of electrochromic thin films of ammonium intercalated vanadium(v) oxide xerogel nanoribbons - Najdoski, Metodija; Koleva, Violeta; Samet, Aksu (Royal Society of Chemistry (RSC), 2014)
A new and simple chemical method for deposition of thin films of ammonium intercalated V2O5·nH2O xerogels has been designed.